A longitudinal study on social support, social participation, and older Europeans' Quality of life. (March 2021) - Lestari, Septi Kurnia; de Luna, Xavier; Eriksson, Malin; Malmberg, Gunnar; Ng, Nawi
Abstract: The association between quality of life (QoL) and social relationships is well established. This paper further analyses whether and how participation in social activities as well as providing and receiving social support, independently, are associated with QoL among the older population in 16 European countries. QoL was measured using the CASP-12 scale. The baseline data came from Wave 6 and the outcome from Wave 7 of the Survey of Health, Ageing and Retirement in Europe (SHARE). The associations of interest were analysed using multivariable linear regression. The effect of possible non-ignorable dropout was tested. Then, doubly robust estimation and sensitivity analyses for unobserved confounding were performed to evaluate the possible causal interpretation of the associations found. Our findings show that participation in at least one of the socially productive activities was positively associated with QoL at two-year follow-up (Average Causal Effect, ACE: 0.474; 95%CI: 0.361, 0.587). The association was stronger among women, people aged 75+, and those in the Southern European region. Providing social support had a positive association with QoL, but only among people aged 75+ (ACE: 0.410; 95%CI: 0.031, 0.789). Conversely, receiving social support had a negative association (ACE: -0.321; 95%CI: -0.448, -0.195) with QoL, especially for men, people aged 75+, and those in Eastern European countries. Sensitivity analyses for unobserved confounders showed that the associations found cannot be attributed to causal effects. Highlights: Association between exposure and outcome was tested using Doubly-robust analysis. Social participation was positively associated with older adults' QoL. Receiving social support was negatively associated with older adults' QoL. Providing social support was positively associated with the QoL of people age 75+ only. The associations observed were sensitive to the unobserved confounders.